A MARKETING BOOKLET FOR MUARA TOURS: A WAY TO PROMOTE ITS STUDY-TOUR PACKAGES - Maria Adeline Cornelius; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
When the writer did her internship at Muara Tours, the writer found that this company had two big problems which affected their business. Muara Tours had failed to advertise study tour packages because Muara Tours does not retain tools that explain the study tour packages. Because of that, the writer comes up with the best solution and the most proper promotional tool which is a marketing booklet. Having a marketing booklet will bring two advantages. First, it assists Muara Tours to advertise study tour packages effectively for the customers. Second, a marketing booklet can use this marketing booklet as a guide for the staff to explain the products. In making this marketing booklet, the writer also considers the potential customers, all aspect in this marketing booklet were simple and attractive. The writer believes that this marketing booklet will assist Muara Tour to lead cooperation between Muara Tour and the customers.